A democracia difícil: violência e irresponsabilidade cívica - Lahuerta, Milton [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
O texto discute a questão da violência que se propaga pela sociedade brasileira, vinculando-a ao problema da “irresponsabilidade cívica”. Para isso, procura resgatar alguns traços que caracterizam a cultura política do país, relacionando-os com a origem escravista de nossa sociedade. Com essa perspectiva são discutidas as dificuldades para a consolidação de uma democracia plena, particularmente no que se refere ao reconhecimento dos direitos e obrigações da cidadania.

This paper discusses the violence issue that is spreading throughout the Brazilian society, with strong connections to the problem of “civic irresponsability”. Thus, some of the traces that portray the political culture of the country are gathered and related to the proslavery origin of that society. The difficulties for the consolidation of democracy are analysed from this perspective, especially those problems that refer to the recognition of the rights and duties of the citizen.
The difficult democracy: violence and civic irresponsability
Keywords: Democracy; Citizenship; Violence; Civic irresponsibility; Authoritarianism; Democracia; Cidadania; Violência; Irresponsabilidade cívica; Autoritarismo